The type B manager : leading successfully in a type A world - Lipman, Victor (Prentice Hall Press, 2015)
"In The Type B Manager, Victor Lipman offers a unique lens through which to view the challenging problems of management. While management has long been considered the realm of Type A individuals--hard-driving, competitive high achievers--all too often these high-intensity traits aren't effective when it comes to motivating your employees. Many characteristics of Type B individuals--being more relaxed, less competitive, more reflective, slower to anger--can be considered "people skills" that better influence motivation and productivity. And successful management after all is the practice of accomplishing work through other people."--provided from Amazon.com.